Extended Nanofluidic Immunochemical Reaction with Femtoliter Sample Volumes. Issue 8 (16th December 2013) - Shirai, Kentaro; Mawatari, Kazuma; Kitamori, Takehiko
<x xml:space="preserve">Abstract</x> The growing need to optimize immunoassay performance driven by interest in analyzing individual cells has resulted in a decrease in the amount of sample required. Miniaturized immunoassays that use ultra‐small femtoliter to attoliter sample volumes, a range known as the extended nanospace, can satisfy this analytical need; however, capturing every targeted molecule without loss in extended nanochannels for subsequent detection remains challenging. This is the first report of a successful extended nanofluidics‐based quantitative immunochemical reaction capable of high capture efficiency using a femtoliter‐scale sample volume. A novel patterning method using a photolithographic technique with vacuum ultraviolet light and low‐temperature (100 °C) bonding enables patterning of functional groups for antibody immobilization before bonding, resulting in an immunochemical reaction space of only 86 fL. Reaction rate analyses indicate a decrease in the required sample volume to 810 fL and improvement in the limit of detection to 3 zmol, 5‐6 orders of magnitude better than possible with the microfluidic immunoassay format. Highly efficient (near 100%) immunochemical reactions on a seconds time scale are possible due to the nm‐scale diffusion length, which should be advantageous for the analysis of ultra‐low‐volume samples.